Pelatihan (Pengimbasan Master Trainer) Keterampilan Berpikir Tingkat Tinggi Guru Mata Pelajaran Matematika SMP Kabupaten Bogor - Indra Bayu Muktyas; Sulistiawati; Muhammad Amin; Fauji Fajarudin (Jurnal Pengabdian Pada Masyarakat, 2022)
TRAINING AS A MASTER DISSEMINATION TRAINER OF HIGH ORDER THINKING SKILLS IN MATHEMATICS IN MIDDLE SCHOOL MATHEMATICS IN BOGOR DISTRICT. The training on Higher Order Thinking Skills (HOTS) for junior high school mathematics teachers in Bogor Regency is based on government policies that include the ability to think at higher levels or HOTS in the National Examination (UN). HOTS itself is part of the PISA international survey. This activity has the aim of whether there is an increase in HOTS training for junior high school mathematics teachers in Bogor Regency after receiving training. This research took place on July 15th to 19th, 2019 at SMP Negeri 2 Cibinong, Bogor Regency. There are two types of participants in this training, namely 5 teachers as master trainers and 23 junior high school mathematics teachers, hereinafter referred to as impact teachers. The five master trainer teachers taught 23 impacted teachers. This training teaches social arithmetic, comparisons, factoring and linear equations, numbers to exponents, and sequences and series. On the sidelines of the learning process, participants were given educational games such as rush hour and logix. Before and after learning, the training participants (23 impacted teachers) were given a test in the form of choices and descriptions. The master trainer is given an assessment by assessing the ability to motivate, mastery of concepts, application of concepts, systematic delivery of concepts, ability to answer questions, ability to provide guidance, and ability to manage classes. The test results show that the significance value obtained is 0.00 < 0.05, which means that there is an increase in the HOTS ability of junior high school mathematics teachers in Bogor Regency after receiving training.